Cocaine associated with onlay bone graft failure: A clinical and histologic report - Shibli, Jamil Awad; Marcantonio, Elcio [UNESP]; Spolidório, Luis Carlos [UNESP]; Marcantonio Júnior, Elcio [UNESP] (Wolters Kluwer, 2005)
This patient report presents an unusual onlay bone graft failure following local cocaine application. Three months after the bone grafting procedure performed in the anterior maxilla for bone volume augmentation, the bone graft was totally exposed in the oral cavity as a result of the rubbing of cocaine on the gingival tissue that covered the bone graft. A histologic view of the removed bone fragment presented not only an area of necrosis but also ample spaces filled with necrosis material and resorption areas. Dental practitioners need to be aware of this phenomenon because such patients often do not report the use of drugs, particularly cocaine. Copyright © 2005 by Lippincott Williams & Wilkins.
Keywords: Autogenous bone graft; Cocaine; Dental implants; Guided bone regeneration/failure; cocaine; adult; bone necrosis; bone transplantation; case report; chemically induced disorder; cocaine dependence; drug effect; edentulousness; follow up; gingiva disease; graft survival; human; incisor; male; maxilla; oral surgery; osteolysis; pathology; Adult; Alveolar Ridge Augmentation; Bone Resorption; Bone Transplantation; Cocaine-Related Disorders; Follow-Up Studies; Gingival Recession; Graft Survival; Humans; Incisor; Jaw, Edentulous, Partially; Male; Maxilla; Osteonecrosis